The development process of a type 2 diabetes health-promoting CBPR intervention - Cecilia Lindsjö; Katarina Sjögren Forss; Christine Kumlien; Anders Kottorp; Margareta Rämgård (Frontiers in Public Health)
IntroductionParticipation is one of the core elements of health promotion, which means that approaches and methods should focus on involvement. The process of involving women with a migration background in health promotion needs to be further explored. Thus, the aim of this study was to explore the development process of a type 2 diabetes health-promotive community-based participatory research intervention among Middle Eastern women with a migration background, living in Sweden.Materials and methodsThis study was performed within the context of a community-based participatory research program in Sweden. The design of this study followed the development process of a community-based participatory research conceptual model, including three of the original four dimensions, that is, the context, the partnership process, and the intervention and research dimension. Appropriate methods for data collection were used in the various dimensions. Participants from the community, active in the program, conducted dialogue cafés, together with the core partners of the program, to inventory existing needs as well as what actions were needed for promoting health and thereby prevent type 2 diabetes.ResultsThe two dialogue cafes resulted in one long term and three short term goals. The third short-term goal—create health circles around food and nutrition was decided to be in focus for this study together with cooperation with the local health care center. The partnership process made it possible to involve relevant collaborators, which resulted in a jointly developed nurse-led educational intervention. Participants and stakeholders were also involved in the process of modifying and elaborating evaluation tools appropriate for the intervention.Discussion/conclusionsThe community-based participatory research approach enables the acknowledgement and use of the various kinds of knowledge of all stakeholders, including the community members. In this study, the community members’ knowledge was obtained through participation and dialogue, aimed at balancing power between stakeholders. This approach, that is, developing a community-based participatory research intervention, offers a possibility for the primary health care to engage with the community members and for other stakeholders to work in a health-promotive way.